The Effect of Small Sided Games Training on the Improvement of Basic Passing and Dribbling Skills in Futsal Extracurricular Students at SMPN 1 Garut - Agus Muhamad Ansori; Irwan Hermawan; Azhar Ramadhana Sonjaya (Indonesian Journal of Sport Management, 2025)
Futsal is a sport that requires players to perform technical skills such as passing and dribbling under high pressure and limited space. However, many students in school futsal extracurricular programs still struggle to perform these skills consistently due to monotonous and less contextual training methods. This condition creates a research gap in developing effective training models that integrate game-like situations to enhance students’ technical performance. Therefore, this study aimed to determine the effect of Small Sided Games (SSG) training on improving basic passing and dribbling skills among futsal extracurricular participants at SMPN 1 Garut. The research employed an experimental method with a pretest-posttest control group design. A total of 24 students were purposively selected and divided into two groups: the experimental group, which received SSG training, and the control group, which followed conventional training. Data were collected using a passing accuracy test and a dribbling zig-zag test and analyzed using normality, homogeneity, and paired sample t-tests with a significance level of 0.05. The results showed a significant improvement in both passing and dribbling skills in the experimental group compared to the control group. These findings indicate that SSG effectively enhances students’ technical abilities, decision-making, and engagement in training. Theoretically, this study reinforces the relevance of contextual learning in sports education. Practically, SSG can serve as an innovative and enjoyable training model for school futsal programs. Future studies are recommended to explore variations of SSG to improve tactical and strategic aspects of futsal performance